The Role of Technology in Advancing Academic Research in STEM in the U.S. - Ravinderjeet Dhillon, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of technology on academic research across STEM disciplines in the United States. As the U.S. maintains its position as a global leader in research and development investment, technological advancements have fundamentally altered how scientific knowledge is created, validated, and disseminated. Digital transformation extends beyond mere efficiency gains, redefining methodological approaches through cloud computing, artificial intelligence, and machine learning applications. The proliferation of open-access repositories has democratized knowledge access while virtual collaboration platforms have enabled unprecedented research partnerships that transcend institutional, disciplinary, and geographical boundaries. However, these advancements have progressed unevenly, creating both opportunities and challenges for equity across the research ecosystem. This article explores the multifaceted dimensions of technology's influence on STEM research, addressing methodological innovations, collaborative frameworks, accessibility considerations, and ethical implications while offering recommendations for researchers, institutions, and policymakers to harness technological potential while ensuring equitable participation in the evolving research landscape.
Keywords: Digital Transformation; Research Methodologies; Scientific Collaboration; Equity in STEM; Responsible Innovation